Ghazaliâ€™s Sufism and Its Influence in Indonesia - Ismail, A Ilyas; Uyuni, Badrah (DINIKA : Academic Journal of Islamic Studies, 2019)
This study aims to describe Ghazaliâ€™s sufism and its influences in Southeast Asia, mainly in Indonesia. Al-Ghazali is a renowned Muslim intellectual who has a special place at every Moslemâ€™s heart, especially in Indonesia. He possesses encyclopedic expertise within various disciplines, ranging from fiqh and ulusulfiqh, al-kalam, logic, philosophy, and sufism. Despite his vast expertise, his practices are more well-known in sufism than in Islamic law, theology, and philosophy due to his long journey, exquisite experience, and groundbreaking thinking within the discipline of Sufism. Ghazali developed a new method of thinking within Islamic epistemology, widely known as Irfani epistemology. One of Ghazaliâ€™s biggest achievements is that Ghazali is considered successful in integrating between Sufism and the fiqh (sharia) Ghazali demonstrated his intellectual brilliance of integrating both branches of Islamic thinking (between sharia and the essence of Islam). Ghazaliâ€™s notable influence and position within the discipline of sufism made him granted the title of â€œHujjat al-Islamâ€.Ghazaliâ€™sSufism spreads and influences the development of Sunni Islam not only in the Arabian peninsula but also in Indonesia and Southeast Asia.